Olfactory bulb‐targeted quantum dot (QD) bioconjugate and Kv1.3 blocking peptide improve metabolic health in obese male mice. Issue 6 (20th October 2020) - Schwartz, Austin B.; Kapur, Anshika; Huang, Zhenbo; Anangi, Raveendra; Spear, John M.; Stagg, Scott; Fardone, Erminia; Dekan, Zolan; Rosenberg, Jens T.; Grant, Samuel C.; King, Glenn F.; Mattoussi, Hedi; et al.
Abstract: The olfactory system is a driver of feeding behavior, whereby olfactory acuity is modulated by the metabolic state of the individual. The excitability of the major output neurons of the olfactory bulb (OB) can be modulated through targeting a voltage‐dependent potassium channel, Kv1.3, which responds to changes in metabolic factors such as insulin, glucose, and glucagon‐like peptide‐1. Because gene‐targeted deletion or inhibition of Kv1.3 in the periphery has been found to increase energy metabolism and decrease body weight, we hypothesized that inhibition of Kv1.3 selectively in the OB could enhance excitability of the output neurons to evoke changes in energy homeostasis. We thereby employed metal‐histidine coordination to self‐assemble the Kv1.3 inhibitor margatoxin (MgTx) to fluorescent quantum dots (QDMgTx) as a means to label cells in vivo and test changes in neuronal excitability and metabolism when delivered to the OB. Using patch‐clamp electrophysiology to measure Kv1.3 properties in heterologously expressed cells and native mitral cells in OB slices, we found that QDMgTx had a fast rate of inhibition, but with a reduced IC50, and increased action potential firing frequency. QDMgTx was capable of labeling cloned Kv1.3 channels but was not visible when delivered to native Kv1.3 in the OB. Diet‐induced obese mice were observed to reduce body weight and clear glucose more quickly following osmotic mini‐pump delivery of QDMgTx/MgTx to the OB, and following MgTx delivery, they increased the use of fats as fuels (reduced respiratory exchange ratio). These results suggest that enhanced excitability of bulbar output neurons can drive metabolic responses. Abstract : The excitability of the major output neurons of the olfactory bulb (OB) can be modulated through targeting a voltage‐dependent potassium channel, Kv1.3, to elicit changes in metabolism. We bound the Kv1.3 inhibitor margatoxin (MgTx) to fluorescent quantum dots (QDMgTx) as a means to label cells in vivo while enhancing neuronal excitability when delivered to the OB. Diet‐induced obese mice had an improved metabolic health following osmotic mini‐pump delivery of QDMgTx/MgTx to the OB, supporting that enhanced excitability of bulbar output neurons can act as a driver of fuel utilization, glucose homeostasis, and body weight set point.